2024
DOI: 10.1371/journal.pone.0294902
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the efficiency, productivity change, and technology gaps of China’s provincial higher education systems: A comprehensive analytical framework

Jiani Liu,
Kim Jungyin,
Shim Jaewoo
et al.

Abstract: China’s higher education system is one of the largest and most complex in the world, with a vast number of higher education institutions scattered across different provinces. Evaluating the efficiency, productivity change, and technology gaps of these institutions is significant for understanding their performance and identifying areas for improvement. In this context, this study employs three different approaches, DEA super-SBM, Malmquist Productivity Index, and Meta-Frontier Analysis, to evaluate the efficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Previous studies have found that there is a relatively obvious imbalance higher education development in China [ 12 14 ]. Meanwhile, considering the economic development in different regions, researchers have also found significant regional differences in digital development [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have found that there is a relatively obvious imbalance higher education development in China [ 12 14 ]. Meanwhile, considering the economic development in different regions, researchers have also found significant regional differences in digital development [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Efficiency and productivity assessments are crucial for organizations seeking continuous improvement and growth in today’s highly competitive and dynamic business environment [ 1 3 ]. Various methodologies and techniques have been developed to evaluate the performance of decision-making units (DMUs) in different areas and applications such as agriculture, banking, communication, education, energy, finance, fishery, forestry, healthcare, insurance, manufacturing, power, supply chain, transportation, and tourism [ 4 6 ].…”
Section: Introductionmentioning
confidence: 99%